2016
DOI: 10.1002/cssc.201600425
|View full text |Cite
|
Sign up to set email alerts
|

By‐Product Carrying Humidified Hydrogen: An Underestimated Issue in the Hydrolysis of Sodium Borohydride

Abstract: Catalyzed hydrolysis of sodium borohydride generates up to four molecules of hydrogen, but contrary to what has been reported so far, the humidified evolved gas is not pure hydrogen. Elemental and spectroscopic analyses show, for the first time, that borate by-products pollute the stream as well as the vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…[387] Petit et al found that the generated H 2 carries borates, and is thus not as pure as what is often claimed. [388] This may explain why Kim and Kim used a third tank (filled with water), called a "wash tank" (Figure 29), [389] in which the generated H 2 was bubbled to be cooled down and to favour the precipitation-solubilisation of the evolving borates. Taking into account the aforementioned technical issues, there is thus a clear need to mature this technology, as it could be ideal for operation in remote areas while avoiding storage systems based on high pressures.…”
Section: One Shoot Hydrogen Delivery Tanksmentioning
confidence: 99%
“…[387] Petit et al found that the generated H 2 carries borates, and is thus not as pure as what is often claimed. [388] This may explain why Kim and Kim used a third tank (filled with water), called a "wash tank" (Figure 29), [389] in which the generated H 2 was bubbled to be cooled down and to favour the precipitation-solubilisation of the evolving borates. Taking into account the aforementioned technical issues, there is thus a clear need to mature this technology, as it could be ideal for operation in remote areas while avoiding storage systems based on high pressures.…”
Section: One Shoot Hydrogen Delivery Tanksmentioning
confidence: 99%
“…In conditions set to get a gravimetric hydrogen‐storage capacity of 4.4 wt % [ x= 4 in Eq. (3)] at 30 °C, at least 10.3 wt % of the B of the starting NaBH 4 was found to evolve with the humidified H 2 stream . This is problematic.…”
Section: Sodium Borohydridementioning
confidence: 99%
“…(3)] at 30 8C, at least 10.3 wt %o ft he Bo ft he startingN aBH 4 was found to evolvew ith the humidified H 2 stream. [64] This is problematic. Fore xample,b orates pluggedt he injector of the gas chromatograph, leading to ab reakdown and a changeo ft he modulus.D eteriorated performancea nd/or breakdown of as caled-ups torage devicea nd that of af uel cell are as likely (e.g.,b locked channels, precipitation onto electrodea nd electrocatalyst).A ne fficient changeable/cleanable filtration system is thus required, which means an additional weightf or the whole storage system and lowered storage capacities.…”
Section: Allegedly Pure Hmentioning
confidence: 99%
“…The borate by-products precipitate and accumulate in the piping, leading to system clogging. Because of the hydrolysis exothermicity (240 ± 5 kJ mol −1 ), 22 water vapor is generated and then sodium cations and borate anions are carried, 23,24 and thus the released H 2 is polluted. Finally, NaBH 4 is expensive.…”
Section: Liquid-state Hydrogen Storagementioning
confidence: 99%